A basic design for automotive crash boxes using an efficient corrugated conical tube. (June 2021) - Mortazavi Moghaddam, Alireza; Kheradpisheh, Atefeh; Asgari, Masoud
Frontal vehicle structure is of high importance through crash energy managements and crash boxes are the fundamental structural component for vehicle safety as well as after sales issues. Similar to many other vehicle components, the detail design of crash box is usually part of manufacture knowhow. However, some guide lines are always available. In this article a general procedure is introduced for designing of crash box with the aid of novel thin walled structures and according to conventional crash scenarios. The problem is followed through some basic steps. Firstly, the crash box idea is selected through a wide range of previous investigated elements and is packaged in a real bench vehicle. Then thanks to the protection provided by the new crash box on the other more expensive components (e.g. headlamp, cooling pack, etc.), the effectiveness of this element are acknowledged through the low speed offset crash. Further on the robustness of new proposed crash box is approved by high speed crash simulations. The quasi-static simulations implemented during the analyses are carried out by finite element explicit code (Abaqus) and the FE modeling and dynamic simulation through the next steps are also performed in ANSA and PAM CRASH respectively. Finally in addition to the general crash box design proposed procedure, the achieved results demonstrated that the corrugated conical thin walled tubes deforms in regular and rather stable shape under both axial and oblique loadings. They also produced a reasonable reaction force versus deformations which leads to stiff and crashworthy energy absorber in comparison to traditional rectangular and even some special models like as origami shapes, and so they could be a valuable selection for crash box implementations in passenger cars.